Services Trade Restrictiveness Index (STRI): Logistics Services - Sugie, Kazuhiro (OECD Publishing, 2015)
This paper presents the services trade restrictiveness indices (STRIs) for logistics services. The STRIs are composite indices taking values between zero and one, zero representing an open market and one a market completely closed to foreign services providers. The indices are calculated for 40 countries, the 34 OECD members and Brazil, the People's Republic of China, India, Indonesia, the Russian Federation and South Africa. The STRIs capture de jure restrictions. This report presents the first vintage of indicators for logistics services and captures regulations in force in 2014. The scores range from 0.08 to 1 for cargo-handling services, 0.04 to 1 for storage and warehouse services, 0.02 to 0.58 for freight transport agency services and 0.03 to 1 for customs brokerage services. It is observed that the regulatory profile differs across countries. In cargo-handling and storage and warehouse services, one country reserves all services provision to a statutory monopoly while another country reserves cargo-handling to a monopoly at port. Freight transport agency has the lowest average score among four subsectors while restrictions on foreign entry, restrictions on the movement of people and regulatory transparency significantly contribute to the results. One country is completely closed to foreign participation in customs brokerage services. The paper presents the list of measures included in the indices, the scoring and weighting system for calculating the indices and an analysis of the results
Keywords: Trade